Recent advances in the role of mesenchymal stem cells as modulators in autoinflammatory diseases - Chen, Baiyu; Chen, Zhilei; He, Mengfei; Zhang, Lijie; Yang, Longyan; Wei, Lingling (Frontiers in Immunology, 2024)
Mesenchymal stem cells (MSCs), recognized for their self-renewal and multi-lineage differentiation capabilities, have garnered considerable wide attention since their discovery in bone marrow. Recent studies have underscored the potential of MSCs in immune regulation, particularly in the context of autoimmune diseases, which arise from immune system imbalances and necessitate long-term treatment. Traditional immunosuppressive drugs, while effective, can lead to drug tolerance and adverse effects, including a heightened risk of infections and malignancies. Consequently, adjuvant therapy incorporating MSCs has emerged as a promising new treatment strategy, leveraging their immunomodulatory properties. This paper reviews the immunomodulatory mechanisms of MSCs and their application in autoimmune diseases, highlighting their potential to regulate immune responses and reduce inflammation. The immunomodulatory mechanisms of MSCs are primarily mediated through direct cell contact and paracrine activity with immune cells. This review lays the groundwork for the broader clinical application of MSCs in the future and underscores their significant scientific value and application prospects. Further research is expected to enhance the efficacy and safety of MSCs-based treatments for autoimmune diseases.